Risk ranking of chemical and microbiological hazards in food - Langerholc, T (EFSA J, 2018)
Risk ranking is a versatile tool used to prioritise activities performed by public health regulatory bodies. It also allows efficient communication between all stakeholders in the process of risk analysis. However, risk ranking methods are still not optimal. Because of the different approaches employed in the risk assessment of microbiological agents and chemicals, it is difficult to rank them together using the same metrics. In our work, we first discuss differences and commonalities between chemical and microbiological risk assessment to provide a starting point for consideration of a common risk ranking platform. In the second part, we perform risk ranking of contaminants and regulated chemicals using the recently developed Risk Thermometer tool. In this approach, chemicals are not ranked solely on the basis of the margin of exposure between a reference value and the exposure, but also by considering the severity of the critical health effects used. The results show that ranking using both methods provides different results from the use of either method alone. Overall, specific chemical groups (i.e. heavy metals, pesticides, etc.) do not generally rank higher or lower, but individual compounds are scattered in the rankings from low to high. Risk ranking methods demand further development to gain wide acceptability and recognition.